ROLE OF JUDICIARY & IMPACT OF LEGALIZATION ON PROSTITUTION IN INDIA - Arora, Girish; Shrivastava , Sonal; Mishra , Monika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The debate over the legalization of prostitution in India is a complex and multifaceted issue. This research article explores the potential socio-economic, legal, and health impacts of legalizing prostitution in the country. It examines international case studies, legal frameworks, and policy implications to understand whether legalization could lead to better working conditions for sex workers or unintended social consequences. The article also considers feminist perspectives, human rights concerns, and public health outcomes in the context of India’s socio-cultural landscape. Prostitution, one of the oldest professions in the world, remains a controversial and complex issue in India. The judiciary has played a crucial role in interpreting laws related to prostitution, balancing the rights of sex workers with public morality and legal principles. This article explores the role of the judiciary in addressing prostitution and examines the potential impact of legalizing prostitution in India. It evaluates the legal framework, judicial pronouncements, and socio-economic consequences of legalization, ultimately assessing whether decriminalization can offer better protection to sex workers.